2013
DOI: 10.1007/s11738-013-1237-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cold-induced changes in the fatty acids profile of rice seedlings

Abstract: Rice, a staple food for more than one half of the world's population, is one of the most cold-sensitive cereals. Breeding programs aimed at increasing rice production are expected to reduce cold-imposed grain losses. Several reports have demonstrated that cold induce differential effects on the fatty acids profile of membranes in chilling-sensitive and chilling-tolerant plants. In this work, we evaluated changes in fatty acid (FA) composition as a potential screening tool to evaluate chilling sensitivity of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…In addition, this tradeoff could arise in part from variation in relative investment in biochemical chilling resistance. Chilling resistance is related to the desaturation degree of the membrane fatty acids 28 , high plasticity of photochemistry 29 , compatible solute concentration 30 , and proteins related to soluble sugar synthesis and antioxidant processes 31 , all of which may potentially decrease the nutrient investment in photosynthetic capacity and contribute to the formation of the trade-off between maximum performance and seasonal maintenance. Additionally, leaves with high photosynthetic capacity generally require high water transport to meet the associated high transpirational demand, which may be associated with greater vulnerability to loss of hydraulic conductance and larger declines in photosynthesis under adverse conditions 32 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this tradeoff could arise in part from variation in relative investment in biochemical chilling resistance. Chilling resistance is related to the desaturation degree of the membrane fatty acids 28 , high plasticity of photochemistry 29 , compatible solute concentration 30 , and proteins related to soluble sugar synthesis and antioxidant processes 31 , all of which may potentially decrease the nutrient investment in photosynthetic capacity and contribute to the formation of the trade-off between maximum performance and seasonal maintenance. Additionally, leaves with high photosynthetic capacity generally require high water transport to meet the associated high transpirational demand, which may be associated with greater vulnerability to loss of hydraulic conductance and larger declines in photosynthesis under adverse conditions 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Rearrangements of cytoskeletal structures in response to low-temperature stress are important for morphological and physiological changes in roots required for the acquisition of freezing tolerance (Kerr and Carter, 1990 ). Plasma membrane lipid alterations such as compositional changes in fatty acids have also been shown as adaptive traits during cold acclimation (Lee et al, 2005 ; Sassaki et al, 2013 ). Exposure of rice roots to low-temperature stress resulted in a gradual increase of root water uptake and induction of genes encoding aquaporins (Ahamed et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…A period of low temperature stress (cold acclimation) induces morphological, physiological, and biochemical changes in both shoot and root tissues that are required for the acquisition of freezing tolerance in cold-tolerant plants (Kerr and Carter, 1990 ; Goulas et al, 2003 ; Hoffmann et al, 2010 ). The alterations in cytoskeletal structures (Kerr and Carter, 1990 ), plasma membrane lipid alterations (Sassaki et al, 2013 ), accumulation of compatible solutes (Castonguay et al, 1995 ) has been shown in the root tissues. Cold acclimation has been shown by upregulation of proteins involved in stress responses and metabolic activities such as glycolysis, nucleoside metabolism, and carbohydrate metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Rice (Oryza sativa L.) is a crucial cereal grain worldwide, serving as a primary source of sustenance for over 50% of the world's population. Around 160 million hectares of agricultural land are dedicated to rice cultivation worldwide [1]. Experts estimate that the production of rice and other crops must increase by over 70% to meet the dietary demands of the world's rapidly growing population by the year 2050.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we used historical rice heat-disaster representations in MLRYR to determine the triggering threshold of heat stress occurrence and characterize single-season rice exposure to heat stress. The main objectives are: (1) to investigate the key phenological stages of rice exposure to heat stress based on the historical disaster data; (2) to quantify the critical temperature threshold for heat stress to single-season rice at different phenological stages; and (3) to delineate the characteristics of heat exposure, which can help us to develop strategies for adaptation to heat stress in MLRYR.…”
Section: Introductionmentioning
confidence: 99%